2000
DOI: 10.1097/00005176-200010000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentations and Predisposing Factors of Cholelithiasis and Sludge in Children

Abstract: The difference in associated conditions may indicate that the pathogenesis of cholelithiasis and sludge differ as well. Furthermore, sludge should be viewed as a dynamic condition not predisposing for the development of gallstones, per se. Cholecystectomy should not be performed routinely but only after careful selection in patients at risk for complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
170
4
37

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(224 citation statements)
references
References 22 publications
13
170
4
37
Order By: Relevance
“…Unlike adults having an asymptomatic disease over 80% (14,15), children are less likely to present with asymptomatic presentation, ranging between 17%-50% (6,12,16). In the present study, the frequency of asymptomatic disease was concordant with the current literature by comprising 38.7% of the entire study population.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Unlike adults having an asymptomatic disease over 80% (14,15), children are less likely to present with asymptomatic presentation, ranging between 17%-50% (6,12,16). In the present study, the frequency of asymptomatic disease was concordant with the current literature by comprising 38.7% of the entire study population.…”
Section: Discussionsupporting
confidence: 89%
“…(1)(2)(3)(4)(5). Although the exact prevalence of gallstones in children is not known, studies have shown an overall prevalence of 0.13% to 1.9% in children (1,6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallstones are increasingly found in childhood, not only because of the use of ultrasonography in the workup of abdominal pain but also because of the increase of incidence in obesity worldwide and the high frequency of hemolytic anemias in all countries [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, gallbladder disease in children was usually observed primarily in patients with comorbid conditions such as hemolytic disorders, parenteral nutrition dependence, or cystic fibrosis [2,3]. However, the cholecystectomy rate in children without the diagnosis of hemolytic anemia has doubled in United States in recent years [4].…”
mentioning
confidence: 99%